New Insights in (Poly)Phenolic Compounds From Dietary Sources to Health Evidences - García-Viguera, Cristina; Domínguez-Perles, Raúl; Baenas, Nieves (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This book is focused on the existing gap between the theoretical bioactivity of (poly)phenols and their real influence in terms of health, once ingested. Due to this, new studies are needed and some examples of new tendencies are included from in vitro and in vivo models which allow for exploring bioaccessibility, bioavailability, and bioactivity, that need to be developed to understand the actual importance of consuming functional foods, rich in these plant secondary metabolites. Moreover, current new strategies need to be developed to enhance the content of these foods, as well as setting up new formulations rich in bioaccessible and bioavailable compounds. Altogether, it could provide a new perspective in therapy, expanding the use of these natural functional compounds, ingredients, and foods in the clinical frame, reducing the use of synthetic drugs. As a result, the joint contribution of multidisciplinary experts from the areas of food science, health, and nutrition, together with the industrial sector, would help to reach these objectives. Taking this into account, diverse studies have been included in this study, which comprises different strategies to approach these objectives from different, complementary, points of view, ranging from the enrichment of by-products in bioactive compounds, through different agricultural techniques, to the assimilation of these compounds by the human body, both in vitro and in vivo, as well as by clinical studies.